Acquired ungual fibrokeratoma. - Armenio, A. (European Journal of Pediatric Dermatology, 2018)
Acquired ungual fibrokeratoma (1) is a benign tumor, on average appearing in the fifth decade of life. However, it may also begin in the pediatric age, without sex predilection. It appears as an asymptomatic, flesh-colored, smooth, hard on palpation papule, which starts from the cuticle at the proximal nail fold and protrudes towards the distal edge (2). The toenails are more frequently affected than finger nails. It can stand on the nail plate, under it or in its context. It can be dome-shaped, rod-shaped as in the current case or branching. Histologically, the epidermis is hyperkeratotic, acanthotic with elongation of the epidermal ridges; the core of the tumor consists of thickened collagen fibers oriented along the longitudinal axis of the neoformation, with a decrease in the elastic fibers and a variable amount of fibroblasts. The tumor should be removed radically, because in some cases it tends to recur.